Sedimentation and Provenance Patterns at an Active Plate Margin: the Cretaceous Xigaze Forearc Basin (Tibet) - Durr, Soren B.; Ricken, Werner; Einsele, Gerard (Journal of Nepal Geological Society, 1995)
The E-W trending Xigaze forearc basin (South Tibet) formed by northward consumption of the Neotethys oceanic lithosphere under Eurasia. About 12 km of elastic sediment (the Xigaze Group) were deposited in the forearc basin, mainly by turbidity currents in five submarine fans. The lower 7 km are preserved in the study area and display three fining-upward supercycles. The Xigaze Group consists dominantly of volcaniclastic sediment with minor hemipelagic, carbonate-rich intercalations. A magmatic arc (Gangdese Belt), positioned on continental crust of the Lhasa Block to the north of the basin, served as major sediment source. The majority of its detritus is andesitic, but tonalitic material appears in younger deposits of the western Xigaze Group, pointing to increasing arc uplift in the west. Erosion of a carbonate shelf is indicated by carbonate clasts in the Xigaze Group. Arc uplift (northern basin flank), as a result of crustal thickening, was low during the Middle Cretaceous, but accelerated in the Late Cretaceous. The subduction complex was unable to serve as outer basin dam (southern basin flank), suggesting its small size. Synsedimentary tectonism is recorded in distal parts of the Xigaze Group and may be related to subduction complex growth, which resulted in evolution from a residual to a composite forearc basin.